Aquilaria species as potential anti-inflammatory agents-A review on in vitro and in vivo studies - A. Eissa, Manar; Hashim, Yumi Zuhanis Has-Yun; Mohd Salleh, Hamzah; Abd Azziz, Saripah Salbiah; Md Isa, Muhammad Lokman; Abd Warif, Nor Malia; Ahmad Nor, Yusilawati; M. El-Kersh, Dina; Abdullah Sani, Muhamad Shirwan (2020)
In the current review article, the studies conducted to investigate the anti-inflammatory activity of Aquilaria species are compiled and summarized. Since inflammation is the underlying cause of many diseases, the encounter of effective and safe biomedical anti-inflammatory compounds has become the focus of recent researches. Aquilaria species were known to possess a wide spectrum of pharmacological activities, among which anti-inflammatory activity has been reported in many in vitro and in vivo studies. Chromones, sesquiterpenoids, flavonoids, benzophenones and phorbol esters were the major anti-inflammatory compounds isolated from Aquilaria species. The objective of this review paper is to extend researches on the anti-inflammatory activity of different parts of Aquilaria species and support their future use in natural pharmaceutical preparations for the treatment of inflammation-associated conditions.